A study on the thermodynamic changes in the mixture of polypropylene (PP) with varying contents of technological and post-user recyclates for sustainable nanocomposites - Michalska-Pożoga, Iwona; Rydzkowski, Tomasz; Mazur, Piotr; Sadowska, Olga; Kumar, Vijay (Elsevier, 2017)
The use of recycled materials can address some of the issues associated with the cost and environmental implications of non-renewable materials. So the prime aim of this work was to determine the thermodynamic changes in the polypropylene (PP) mixtures depending on the percentage amount of different origin recyclates for sustainable nanocomposites. In this study, different polypropylene mixtures with the addition of PP recyclates from a selective waste collection system and in-plant recycling system have been subjected to detailed analysis. It was obvious that recyclates from technological waste were of higher quality than post-user recyclates obtained from a selective waste collection system. The influence of the source of the recyclates on the different properties of the processed materials has been studied in detail. The content of the repeatedly processed material in the technological recyclates was found to explain the unexpected influence of the recyclates content on the properties of the final product. A mathematical model was also formulated to calculate the content of the material with certain amount of recirculations in the in-plant recycling system since no analyses concerning the content of the repeatedly processed material in the technological recyclates added to the original material were found in the literature.
Keywords: Polypropylene; Nanocomposites; Recycling; Recyclates; Thermal properties; Processing properties